226. An Emergency Department Antimicrobial Stewardship Intervention to Improve Antibiotic Selection and Duration for Skin and Soft-tissue infections in Adult and Pediatric Outpatients. (26th November 2018) - May, Larissa; Tancredi, Dan; Mooso, Benjamin; Nguyen, Megan; Ondak, Susan; Anderson, Chance; Briggs, Jennifer; Luong, Linh; Miller, Loren G
Abstract: Background: Skin and soft-tissue infections (SSTIs) are common infections seen in the Emergency Department (ED). However, adherence to IDSA guidelines for treatment, in terms of antibiotic selection and duration, is poor. Objective . To evaluate the ability of a multifaceted intervention to improve adherence to the 2014 IDSA guidelines for the management of SSTIs in an academic adult and pediatric ED. Methods: A non-randomized study of a multifaceted intervention for SSTI in the ED was employed which included educational presentations, implementation of an electronic order set based on 2014 IDSA guidelines, dissemination of ED-specific antibiograms, monthly departmental peer comparisons, and bimonthly individual feedback. SSTI visits were identified using ICD-10 codes L00, L02.x1, L03, L08.89, and L08.9. The primary endpoint was adherence to IDSA guidelines. Outcomes during the preintervention and intervention periods, adjusting for patient demographics and infection characteristics, were compared with the same time periods at a control site (CS) that did not implement the intervention. Results: There were 583 SSTIs included in the study [intervention site (IS) =283, CS =300] split over three time periods: preintervention (October 2015–March 2016; IS = 130, CS = 150), intervention (October 2016–March 2017; IS = 99, CS = 150), and postintervention (April 2017–July 2017; IS = 54, CS = 0). At the IS, adherence was 41% prior to the intervention and 51% during the intervention. At the CS adherence was 19% and 25% during the two time periods. In the adjusted model, adherence at the IS was higher during the intervention compared with the preintervention period [adjusted odds ratio (aOR) 2.26 (95% CI 1.24–4.10)]. Adherence in the postintervention period was similar to the preintervention period [aOR 0.94 (0.45–1.97)]. No changes were seen during the two time periods at the CS [aOR 1.00 (0.53–1.89)]. Conclusion: Implementation of an antimicrobial stewardship intervention for SSTI significantly improved adherence to IDSA guidelines; however, adherence regressed after the intervention ended. Additionally, adherence was generally poor in all time periods and at both sites. Further research is needed to understand barriers and challenges to implementation of SSTI guidelines in ED settings. Disclosures: L. G. Miller, Merck: Grant Investigator, Research grant